ANALYSIS OF HEDGING DETERMINANTS WITH FOREIGN CURRENCY DERIVATIVE INSTRUMENTS ON COMPANIES LISTED ON BEI PERIOD 2012-2015 - Ahmad, Gatot Nazir; Mardiyati, Umi; Nashrin, Ahmad Shofi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
This study is conducted to see the effect of the company's firm size, growth opportunities, leverage and liquidity on the decision of hedging with foreign currency derivative instruments on manufacturing companies listed on the Indonesian Stock Exchange (BEI) period 2012-2015. The Data that is used on this study is a set of data panel with purposive sampling method, and the criteria for the sample is: (1) manufacturing companies listed on the Stock Exchange period 2012 to 2015, (2) manufacturing companies that has transaction exposure ( liabilities and / or assets denominated in foreign currency, (3) manufacturing companies that has the data is needed for this study. The total sample of this study is 106 companies or 424 observation within 4 years. The Data analysis technique that is used on this study is logistic regression with z-statistic as hypotheses testing to test the regression coefficient with an alpha of 5%. The study result shows that firm size, growth opportunities and liquidity positively and Significantly Affect the decision of hedging with foreign currency derivative instruments, while leverage negatively and insignificantly Affect the decision of hedging with foreign currency derivative instruments. Key words: firm size, growth opportunities, leverage, liquidity, hedging, derivatives, risk management